(untitled) (South East Asia Journal of Public Health, 2013)
Bangladesh has made significant progress in many of its social development indicators particularly in health; however, a vast portion of its people still does not use health care services from medically trained providers. An attempt has been made in this study to investigate levels and patterns of health care exclusion among women in Bangladesh. A face to face cross-sectional survey was carried out in a total of 674 married women, selected with the convenience sampling technique. This study was carried out in Bancharampur sub-district under Bramman Baria district and Mirpur sub-district under Dhaka district from 1st July to 30th July in 2010. Results revealed that the mean health care exclusion score was 14.0 (SD=4.40) out of 21. The least used reason to explain health care exclusion was A doctor recommended a surgery for a family member but we did not have it done, with only 9.9% of the subjects giving this reason. The most common reason was A child in the family was sick but was unable to obtain the required health care (32.6%). Multivariate regression analysis found that the independent variables explained 37.8% of variance. Significant association of health care exclusion appeared with the participants’ level of education (B= -0.183, CI= -0.264 to -0.102), the familys wealth status (B= -0.803, CI= -0.970 to -0.637), family size (B=0.315, CI=0.214 to 0.416), exposure to mass media (B=0.415, CI=0.218 to 0.612) and history of health care service use (B=1.971, CI=1.238 to 2.705). It is suggested that women’s education specific to health care utilization, increasing health related mass media exposure and providing counselling on positive aspects of health care by health professionals to the patients coming to the clinic are necessary to reduce health are exclusion. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13208 South East Asia Journal of Public Health 2011:1:17-23